2017
DOI: 10.1111/acem.13132
|View full text |Cite
|
Sign up to set email alerts
|

History, Physical Examination, Laboratory Testing, and Emergency Department Ultrasonography for the Diagnosis of Acute Cholecystitis

Abstract: Variable disease prevalence, coupled with limited sample sizes, increases the risk of selection bias. Individually, none of these investigations reliably rule out AC. Development of a clinical decision rule to include evaluation of H&P, laboratory data, and US are more likely to achieve a correct diagnosis of AC.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
0
3

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 47 publications
(35 citation statements)
references
References 41 publications
(114 reference statements)
1
31
0
3
Order By: Relevance
“…Multiple studies have examined the diagnostic accuracy of history, physical examination, and laboratory tests for cholecystitis 6 and a meta-analysis quantitatively showed that POCUS consistently surpassed all other bedside investigations for sensitivity for the diagnosis of biliary disease. 7 Additionally, POCUS has been studied for accuracy with a recent systematic review showing the sensitivity and specificity for cholelithiasis is 89.8% and 88.0%, respectively. 8 POCUS has also been assessed for the diagnosis of acute cholecystitis and found to be highly sensitive and specific (87% and 82%) when the criteria of gallstones plus an additional finding of a sonographic Murphy’s sign, gallbladder wall thickness, or pericholecystic fluid is used for assessment.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies have examined the diagnostic accuracy of history, physical examination, and laboratory tests for cholecystitis 6 and a meta-analysis quantitatively showed that POCUS consistently surpassed all other bedside investigations for sensitivity for the diagnosis of biliary disease. 7 Additionally, POCUS has been studied for accuracy with a recent systematic review showing the sensitivity and specificity for cholelithiasis is 89.8% and 88.0%, respectively. 8 POCUS has also been assessed for the diagnosis of acute cholecystitis and found to be highly sensitive and specific (87% and 82%) when the criteria of gallstones plus an additional finding of a sonographic Murphy’s sign, gallbladder wall thickness, or pericholecystic fluid is used for assessment.…”
Section: Introductionmentioning
confidence: 99%
“…In the COVID-19 pandemic period, as a disease severity laboratory test for many inflammatory diseases such as acute cholecystitis and acute appendicitis, acute-phase reactants including leukocyte and CRP are expected to increase because of possible delayed hospital admissions of patients 16 . Also, in the COVID-19 disease, it is known that the laboratory findings of leukopenia and high CRP are seen, but in this situation for the differential diagnosis, the clinical presentation of the patient is much more important 17 .…”
Section: Discussionmentioning
confidence: 99%
“…6 Murphy's sign sensitivity was 62% and specificity was 96% for acute cholecysitis diagnosis. 7 The diagnosis is made based on this clinical features and supported by findings from relevant laboratory and imaging studies. The triad of sudden onset of RUQ pain, fever, and leukocytosis is highly suggestive of acute cholecystitis.…”
Section: Discussionmentioning
confidence: 99%